Scale insects on yams in Benin: diversity, incidence and farmers' knowledge and perceptions - Goergen, Georg E.; Dossou, R.; Asiedu, Robert; Hanna, R. (International Association of Hydrological Sciences, 2012)
Yam (Dioscoreaspp.) is a primary agricultural commodity and a traditional staple food over much of West and Central Africa, where it is highly profitable both for producers and traders especially when production and storage strategies are successful in securing the supply of urban markets throughout the year. Insect pests such as mealybugs of the genus Planococcus Ferris (Hem.: Pseudococcidae) and the scale Aspidiellahartii (Cockerell) (Hem.: Diaspididae) can become major constrains causing significant yield losses both in the field and in storage. Detailed information on the pest status of the scale insects on yams and farmers' knowledge and perceptions of these insects were assessed in two surveys carried out in central and southern Benin in May and December 2009. In the May survey, covering134 sites and 68 villages, scale infestations were found in 68% of yam stores and sales points with in average 41% of the tubers infested. Lower incidence and infestation rates were observed at the main harvest period in December when scale and mealybug infestations were found in 56% of the 102 fields from 68 villages with an average of 23% infested tubers, indicating that scale and mealybug infestations are initiated in the field. Aspidiellahartii tended to become proportionally more important in stores increasing from 9 to 40% of the recovered scale insect pests. In both surveys the percentage of mixed infestations remained relatively low - at 13 and 5% for the first and second survey respectively. Structured questionnaires performed at every site showed that almost all farmers and traders were able to recognize yam scales and mealybugs and ranked both groups equally in importance as pests. The presence of the scale insects was generally regarded as having a negative impact on the quality of stored tubers, especially their germination rate when used as seeds for planting new fields. Whereas all cultivars seemed to be at risk from scale insects, late varieties, appeared to be more susceptible than other varieties. Farmers estimated an average of 22% reduction of the total yield and 23% reduction in planting material due to scale insect infestations. Tuber rot, theft, cattle feed and bush fire were recurrently cited as the most important problems of stored yams. Interestingly, 66% of the questioned farmers believed scale infestations have been on the rise over the last few years, while at the same time the length of fallow periods were on the decline primarily because of increasing pressure on the land which might suggest a relationship between scale infestation and fallow period. Farmers, however, differed considerably in their admission that such a relationship is real. Taken together, both field evidence and farmers perceptions of scale insect infestations on yams are a first and valuable step in the development of appropriate management practices to reduce yam losses due to scale insect infestations. Control options are presently limited to preventive actions such as early harvest, culling of infested tubers, selective early consumption, and production of yam chips.